The Influence of Understanding the Language of Love on the Resilience of Young Muslim Gen Z Families: An Exploratory Mixed-Methods Approach - Mufida, Syifa; Huda, Nuril (Jurnal Inovasi Pendidikan Agama Islam (JIPAI), 2025)
This study aims to analyze the influence of understanding the language of love on the resilience of young Muslim Generation Z families. The rising trend of divorce among young people in Indonesia, including among Muslims of all generations, highlights the importance of examining the affective aspects and emotional communication within families. This study employs a mixed-method approach with a sequential exploratory design, beginning with a qualitative study followed by a quantitative phase. The study focuses on Muslim Generation Z couples residing in Banjarmasin City, South Kalimantan Province. In the qualitative phase, interviews were conducted with five Muslim Generation Z married couples to explore the dynamics of love languages and marital resilience. These findings served as the basis for developing a quantitative survey instrument, which was distributed to 102 respondents. Quantitative data analysis revealed that the most dominant love languages were Acts of Service (70.6%) and Physical Touch (69.6%). Pearson's correlation indicated a moderate positive relationship between understanding of love languages and the level of family resilience among young Muslim couples (r = 0.56). Respondents who felt understood in their love language tended to have more effective communication, higher emotional bonds, and the ability to resolve conflicts more maturely. The practical implications of these findings are important for educational institutions, religious counselors, and family coaches in nurturing a resilient and harmonious young generation of Muslim families.